2001
DOI: 10.1021/ef000263e
|View full text |Cite
|
Sign up to set email alerts
|

Solid−Liquid−Vapor Phase Boundary of a North Sea Waxy Crude:  Measurement and Modeling

Abstract: The wax appearance temperature as well as the liquid vapor phase boundary were measured on two condensate gases from a high-temperature-high-pressure field in the North Sea. Measurements were performed up to 45 MPa in the temperature range from 293 to 423 K. The experimental temperatures of wax appearance were then compared to the prediction of a model previously developed for synthetic light gas-heavy n-paraffins systems and adapted here to the representation of live oils.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 31 publications
2
61
0
Order By: Relevance
“…The second example is a North Sea HP-HT reservoir fluid (mixture GC-B from Daridon et al [40]). The initial reservoir pressure is 1100 bar and the reservoir temperature is 459 K. Mixture composition is characterized by 40 components, among which 25 components (paraffins from C 11 to C 35 ) precipitate in the solid phase.…”
Section: North Sea Gas Condensatementioning
confidence: 99%
See 1 more Smart Citation
“…The second example is a North Sea HP-HT reservoir fluid (mixture GC-B from Daridon et al [40]). The initial reservoir pressure is 1100 bar and the reservoir temperature is 459 K. Mixture composition is characterized by 40 components, among which 25 components (paraffins from C 11 to C 35 ) precipitate in the solid phase.…”
Section: North Sea Gas Condensatementioning
confidence: 99%
“…The initial reservoir pressure is 1100 bar and the reservoir temperature is 459 K. Mixture composition is characterized by 40 components, among which 25 components (paraffins from C 11 to C 35 ) precipitate in the solid phase. All required elements for the fluid description can be found in [36,40]. Figure 2 presents the phase envelope (calculated and experimental points) and the calculated JTIC.…”
Section: North Sea Gas Condensatementioning
confidence: 99%
“…The two last fluids (6-CG and 7-CG) are two condensate gases from a high-temperature/high-pressure field in the North Sea for which Daridon et al 23 reported fluid-solid-phase transition above and below the dew point. For these fluids no measurements were performed on the condensate gases at atmospheric pressure.…”
Section: Atmospheric Pressure Fitting Proceduresmentioning
confidence: 99%
“…Another model, based on the formation of a solid solution that uses a cubic equation of state (EOS) with the LCVM (linear combination of HuronVial and Michelsen) mixing rule for the description of the fluid phases 21 and the Wilson equation 22 for describing the solid solution nonideality, has been developed and was shown to accurately predict the onset of crystallization as well as the amount of solid precipitate as a function of temperature and pressure in both synthetic systems 1 and crude oils. 23 Unfortunately, this last model, which calculates the fluid-solid-phase equilibria with good accuracy, is difficult to implement in multiflash algorithms used in the petroleum industry because of the use of the G E mixing rule as well as group contribution. This reduces the interest of the model, in spite of its success and reliability, for regular application in the petroleum industry.…”
Section: Introductionmentioning
confidence: 99%
“…conditions [1][2][3]. In particular, for methane-rich fluids under high pressure-high temperature conditions, the retrograde condensation may sometime cause heavy organic deposition even with fluids with low heavy component content [4][5][6]. Thus, gas depressurization may increase the wax appearance temperature by as much as 10 K from saturation to atmospheric pressure in some crude oils [5,7].…”
Section: Introductionmentioning
confidence: 99%